Biomechanics and Load Resistance of Short Dental Implants: A Review of the Literature. (8th May 2013) - Hasan, Istabrak; Bourauel, Christoph; Mundt, Torsten; Heinemann, Friedhelm
Abstract : This paper was aimed to review the studies published about short dental implants. In the focus were the works that investigated the effect of biting forces of the rate of marginal bone resorption around short implants and their survival rates. Bone deformation defined by strain was obviously higher around short implants than the conventional ones. The clinical outcomes of 6 mm short implants after 2 years showed a survival rate of 94% to 95% and lower survival rate (<80%) for 7 mm short implants after 3 to 6 years for single crown restorations. The short implants used for supporting fixed partial prostheses had a survival rate of 98.9%. Short implants can be considered as a good alternative implant therapy to support single crown or partial fixed restorations.